Negative controls to detect uncontrolled confounding in observational studies of mammographic screening comparing participants and non-participants. (25th March 2020) - Lousdal, Mette Lise; Lash, Timothy L; Flanders, W Dana; Brookhart, M Alan; Kristiansen, Ivar Sønbø; Kalager, Mette; Støvring, Henrik
Abstract: Background: When comparing mammography-screening participants and non-participants, estimates of reduction in breast-cancer mortality may be biased by poor baseline comparability. We used negative controls to detect uncontrolled confounding. Methods: We designed a closed cohort of Danish women invited to a mammography-screening programme at age 50–52 years in Copenhagen or Funen from 1991 through 2001. We included women with a normal screening result in their first-invitation round. Based on their second-invitation round, women were divided into participants and non-participants and followed until death, emigration or 31 December 2014, whichever came first. We estimated hazard ratios (HRs) of death from breast cancer, causes other than breast cancer and external causes. We added dental-care participation as an exposure to test for an independent association with breast-cancer mortality. We adjusted for civil status, parity, age at first birth, educational attainment, income and hormone use. Results: Screening participants had a lower hazard of breast-cancer death [HR 0.47, 95% confidence interval (CI) 0.32, 0.69] compared with non-participants. Participants also had a lower hazard of death from other causes (HR 0.43, 95% CI 0.39, 0.46) and external causes (HR 0.35, 95% CI 0.23, 0.54). Reductions persisted after covariate adjustment. Dental-care participants had a lower hazard of breast-cancer death (HR 0.75, 95% CI 0.56, 1.01), irrespective of screening participation. Conclusions: Negative-control associations indicated residual uncontrolled confounding when comparing breast-cancer mortality among screening participants and non-participants.